Methotrexate Reduces the Probability of Discontinuation of TNF Inhibitors in Seropositive Patients With Rheumatoid Arthritis. A Real-World Data Analysis - Hernández-Breijo, Borja; Brenis, Claudia M.; Plasencia-Rodríguez, Chamaida; Martínez-Feito, Ana; Novella-Navarro, Marta; Pascual-Salcedo, Dora; Balsa, Alejandro (Frontiers in Medicine, 2021)
Tumor necrosis factor inhibitors (TNFi) are widely used for the treatment of patients with rheumatoid arthritis (RA), however a considerable percentage of patients discontinued the therapy. The aim of this study is to explore real-world TNFi survival, stratified for seropositivity, and to determine the factors that may influence it. This is a retrospective, observational and longitudinal study, using real-world data of patients, who started their first TNFi therapy between 1999 and 2018 from the RA-PAZ cohort. Patients were considered seropositive if they showed positive serum levels of either RF, ACPA or both. Treatment survival was analysed using Kaplan-Meier curves, and Cox proportional hazards models were used to compare the risks of TNFi discontinuation for seronegative and seropositive patients. Of the included 250 patients, 213 (85%) were seropositive. Results showed that TNFi survival did not depend on seropositivity status. However, median survival time was significant longer for seropositive patients who received concomitant MTX compared to patients who did not receive it (median [95% CI]: 3.3 yr [2.3 to 4.2] vs 2.6 yr [1.7 to 3.6], respectively; p=0.008). Furthermore, seropositive patients who received concomitant MTX were 49% less likely to discontinue TNFi therapy than patients who did not receive it (HR: 0.51; 95% CI: 0.35-0.74). In addition, we found that in seropositive patients, the use of prednisone throughout the TNFi treatment was associated with a higher likelihood of therapy discontinuation (OR: 2.30; 95% CI: 1.01-5.23). In conclusion, these data provide evidence to support the use of concomitant MTX in seropositive patients to prolong the effectiveness and the survival of the TNFi therapy. Moreover, the co-administration of prednisone in seropositive patients receiving TNFi was highly associated with TNFi discontinuation.